â€œEco Green Ular Tangga (EGUT)â€ Game as Tools of Teaching to improve Environmental Care for Early childhood in Tunas Bangsa and Jati Asih Play Groups in Semarang - Retno Sawitri, Dian; E, Noersasongko; D.N, Izzati (Universitas Negeri Semarang, 2019)
PAUD (Play Groups) Tunas Bangsa and PAUD Jati Asih are institutions that position parents as partners in the preparation and personal development from an early age, providing guidance to play groups and kindergartens in the Ngaliyan area of Semarang. Two institutions of Early Childhood Education that will become partners in the Community Partnership Program (PKM). Dra. Tri Edi Mhanani as the principal of Tunas Bangsa PAUD school and Ibu Sri Lestari Raahayu P., A.Md as the principal of Jati Asih PAUD school have the same topic, namely not having education related to environmental goals.Â Educational props of the ladder snake game (EGUT) can help improve children's cognitive and psychomotor abilities. Children will learn to analyze colors, recognize letters, socialize, jump, throw, all of which are positive things in children's development. The material and features provided can help children to love the environment.